Novel portable hypothermic machine perfusion preservation device enhances cardiac viability of donated human hearts - Andrijauskaite, Kristina; Veraza, Rafael J.; Lopez, Riley P.; Maxwell, Zach; Cano, Isabella; Cisneros, Exal E.; Jessop, Israel J.; Basurto, Maria; Lamberson, George; Watt, Michelle D.; Nespral, Joseph; Ono, Masahiro; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Heart transplant remains the gold standard treatment for patients with advanced heart failure. However, the list of patients waiting for a heart transplant continues to increase. We have developed a portable hypothermic oxygenated machine perfusion device, the VP.S ENCORE®, to extend the allowable preservation time. The purpose of this study was to test the efficacy of the VP.S. ENCORE® using deceased donors derived hearts. Methods Hearts from brain-dead donors not utilized for transplant (n = 11) were offered for research from the Texas Organ Sharing Alliance (TOSA), South and Central Texas' Organ Procurement Organization (OPO) and were preserved in the VP.S ENCORE® for 4 (n = 2), 6 (n = 3), and 8 (n = 3) hours or were kept in static cold storage (SCS) (n = 3). After preservation, the hearts were placed in an isolated heart Langendorff model for reperfusion and evaluated for cardiac function. Results The mean donor age was 37.82 ± 12.67 with the youngest donor being 19 and the oldest donor being 58 years old. SCS hearts mean weight gain (%) was −1.4 ± 2.77, while perfused at 4 h was 5.6 ± 6.04, perfused at 6 h 2.1 ± 6.04, and 8 h was 7.2 ± 10.76. Venous and arterial lactate concentrations were less than 2.0 mmol/L across all perfused hearts. Left ventricular contractility (+dPdT, mmHg/s) for 4 h (1,214 ± 1,064), 6 (1,565 ± 141.3), and 8 h (1,331 ± 403.6) were within the range of healthy human heart function. Thus, not significant as compared to the SCS group (1,597 ± 342.2). However, the left ventricular relaxation (mmHg/s) was significant in 6-hour perfused heart (p < 0.05) as compared to SCS. Gene expression analysis of inflammation markers (IL-6, IL-1β) showed no significant differences between SCS and perfused hearts, but a 6-hour perfusion led to a downregulated expression of these markers. Discussion The results demonstrate that the VP.S ENCORE® device enhances cardiac viability and exhibits comparable cardiac function to a healthy heart. The implications of these findings suggest that the VP.S ENCORE® could introduce a new paradigm in the field of organ preservation, especially for marginal hearts.